Autonomus Call System Berbasis ESP32 Untuk Peringatan Dini Kebakaran Rumah - Nurrohim, Roziq; B. Kharisma, Oktaf (Jurnal Sistem Cerdas, 2023)
Fires can occur anywhere, both in buildings and in residential areas. Fires often occur due to human negligence caused by many factors, such as large or small LPG cylinder leaks, the danger of disposing of cigarette butts, and electrical short circuits, causing fire and spreading to other parts. The problem that often arises so far is that the information received about the location of the fire is often wrong, so the fire department arrives late to the actual fire location, therefore a tool is needed to provide an early warning system for house fires. Based on the above problems, we propose a tool that can make calls automatically to provide accurate fire information such as address coordinates to firefighters and early warning of gas leaks to homeowners. This tool uses the ESP32 as a microcontroller, a fire sensor, and MQ2 as the main sensor, Thiger.IO monitors data sensors, telegram messages, email notifications, and phone calls using SIM 800L. The results of this tool can detect gas leaks when gas levels greater than 400 PPM, and a fire occurs with a maximum fire detection distance of 250 cm. Telegram notifications sent in real-time to homeowners, phone calls, and emails of fire address information to the firefighter worked great. The average response time for telephone calls is 6.59 seconds, and a success percentage of 100% obtained in making telephone calls with stable signal conditions.